Managing nonprofit organizations - Tschirhart, Mary, 1960-; Bielefeld, Wolfgang; ProQuest (Firm) (San Francisco : Jossey-Bass, 2012)
"Managing Nonprofit Organizations offers a comprehensive treatment of the key topics in nonprofit management for practitioners, professors, and students in both graduate and undergraduate courses. This groundbreaking volume serves as both text and handbook and includes supplemental online materials and additional cases. The authors Tschirhart and Bielefeld (two of the top scholars in nonprofit management) bring theory and practice together in a cohesive way so readers are both informed and interested"--
Machine generated contents note: Preface, Acknowledgments, Part I: Overview; Chapter 1: Understanding Nonprofit Organizations and Social Entrepreneurship; Chapter 2: Challenges of Effective and Ethical Organizational Design and Management; Chapter 3: Managing in a Dynamic Stakeholder Environment; Part II: Organizational Stages: Design and Start-up to Closure; Chapter 4: The Founding Impulse; Chapter 5: The Nonprofit Business Case; Chapter 6: Innovation, Change and Growth; Chapter 7: Nonprofit Closure, Conversion and Merger; Part III. Organizational Elements; Chapter 8: Organizational Design; Chapter 9: The Executive Director and Staff (Paid and Volunteer); Chapter 10: Board Governance; Chapter 11: Membership; Chapter 12: Financial Resources and Attraction of Fees, Contracts, Grants, and Donations; Chapter 13: Strategic Partnerships and Affiliations; Part IV: Organizational Activities; Chapter 14: Strategic Planning and Decision-Making; Chapter 15: Programming and Marketing; Chapter 16: Public Relations and Communications; Chapter 17: Relationships with Government; Chapter 18: Evaluation of Nonprofit Organizations; Appendix A. Nonprofit Management Education; Subject Index; Author Index.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Nonprofit organizations -- Management; Electronic books